2016
DOI: 10.1007/s40261-016-0401-3
|View full text |Cite
|
Sign up to set email alerts
|

Economic Evaluation of Intravenous Immunoglobulin plus Corticosteroids for the Treatment of Steroid-Resistant Chronic Inflammatory Demyelinating Polyradiculoneuropathy in Thailand

Abstract: At a threshold of US$4672 per QALY gained, IVIG plus corticosteroids is considered a cost-effective treatment for steroid-resistant CIDP patients in Thailand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…A recent meta-analysis concluded that subcutaneous and intravenous immunoglobulin are equally effective in CIDP and in multifocal motor neuropathy (Racosta 2016). The ongoing Van Schaik 2016 RCT is also investigating the efficacy of subcutaneous immunoglobulin and the next updates of Eftimov 2013 and this overview will include this trial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent meta-analysis concluded that subcutaneous and intravenous immunoglobulin are equally effective in CIDP and in multifocal motor neuropathy (Racosta 2016). The ongoing Van Schaik 2016 RCT is also investigating the efficacy of subcutaneous immunoglobulin and the next updates of Eftimov 2013 and this overview will include this trial.…”
Section: Discussionmentioning
confidence: 99%
“…A Canadian study estimated the incremental cost per QALY gained of IVIg compared with corticosteroids as CAD 687,287 (approximately USD 535,800) (Blackhouse 2010). By contrast, based on societal willingness-to-pay thresholds, a study in Thailand concluded that IVIg is a cost-effective treatment for corticosteroid-resistant CIDP (Bamrungsawad 2016). Nevertheless, in many countries IVIg is not an affordable option, whereas plasma exchange can be a more available and affordable alternative to corticosteroids.…”
Section: Discussionmentioning
confidence: 99%
“…From previous study, the estimated cost of 12-week maintenance IVIg was 3,199 US dollars (body weight 50 kg) and the estimated cost of prednisolone plus azathioprine was 741 US dollars. 22 A similar study in Canada also found that IVIg was not perceived as cost-effective for first line treatment for CIDP, similar to study in Thailand. 22,23 Due to the absence of IVIg indication in autoimmune encephalitis and NMOSD, the patient could not reimburse the cost of treatment.…”
Section: Discussionmentioning
confidence: 52%
“…22 A similar study in Canada also found that IVIg was not perceived as cost-effective for first line treatment for CIDP, similar to study in Thailand. 22,23 Due to the absence of IVIg indication in autoimmune encephalitis and NMOSD, the patient could not reimburse the cost of treatment. They then have to pay out of pocket and decide between the treatment options of IVIg and plasmapheresis.…”
Section: Discussionmentioning
confidence: 52%